Beyond the Fold: Emerging Biological Applications of DNA Origami. (6th April 2016) - Chandrasekaran, Arun Richard; Anderson, Nate; Kizer, Megan; Halvorsen, Ken; Wang, Xing
Abstract: The use of DNA as a material for nanoscale construction has blossomed in the past decade. This is largely attributable to the DNA origami technique, which has enabled construction of nanostructures ranging from simple two‐dimensional sheets to complex three‐dimensional objects with defined curves and edges. These structures are amenable to site‐specific functionalization with nanometer precision, and have been shown to exhibit cellular biocompatibility and permeability. The DNA origami technique has already found widespread use in a variety of emerging biological applications such as biosensing, enzyme cascades, biomolecular analysis, biomimetics, and drug delivery. We highlight a few of these applications and comments on the prospects for this rapidly expanding field of research. Abstract : A little beauty is Science : DNA origami is a versatile technique for the construction of two‐ and three‐dimensional nanostructures. The ability to functionalize these nanostructures makes them useful for a variety of biological applications such as biosensing, enzyme cascades, biomolecular analysis and drug delivery.